Characterization of Co-infection With Fowl Adenovirus Serotype 4 and 8a - Liu, Jingyi; Shi, Xinjin; Lv, Lu; Wang, Kai; Yang, Zhiwei; Li, Yunzhang; Chen, Hongjun (Frontiers in Microbiology, 2021)
Fowl adenoviruses (FAdVs), which are distributed worldwide, have caused considerable economic losses to poultry farms. Co-infection with FAdVs and other avian pathogens has been reported previously. However, the pathogenicity of different serotypes of FAdVs causing co-infection remains unclear. Herein, strain HN from FAdV species C serotype 4 (FAdV-4) and strain AH720 from species E serotype 8a (FAdV-8a) were used to assess the pathogenicity of their co-infection in SPF chickens. Compared with chickens infected with FAdV-4 alone, those co-infected with FAdV-4 and FAdV-8a showed similar clinical symptoms, mortality rates and degree of tissue lesions and notably decreased viral loads of HN. Conversely, the viral loads of AH720 increased markedly in the co-infection group compared with that in chickens infected with AH720 virus alone. Increased viral loads of AH720 in the liver were suspected to contribute to the pathogenicity of chickens co-infected with the HN and AH720 strains. This was further investigated by histopathology and TUNEL staining analyses. Collectively, these data indicated that co-infection with FAdV-4 and FAdV-8a suppresses the replication and proliferation of FAdV-4 but enhances the replication and proliferation of FAdV-8a in chicken liver. This study will provide valuable information for the further investigation of the interactions between FAdV-4 and FAdV-8a during co-infection.